Agar Underlay Method for Recovery of Sublethally Heat-Injured Bacteria - Kang, D. H. (American Society for Microbiology, 1999)
A method of recovering sublethally heat-injured bacteria was developed. The procedure (termed the agar underlay method) uses a nonselective agar underlaid with a selective medium. In a two-chambered petri dish, the Lutri plate (LP), a nonselective agar is inoculated with a population of sublethally heat-injured bacteria. After a 2-h repair incubation period, selective agar is added to the bottom chamber of the LP and incubated. By diffusing through the nonselective top agar, selective agents from the underlay medium impart selectivity to the system. By the agar underlay method, recovery rates of the heat-injured food-borne pathogens Escherichia coli O157:H7 and Salmonella typhimurium were not different (P > 0.05) from recovery rates determined with nonselective media. Sublethally heat-injured cells (60°C for 1.5 min in buffer or 80°C for 30 s on meat surfaces) grew and produced a typical colony morphology and color reaction when the agar underlay procedure was used with the appropriate respective selective agars. Unlike agar overlay methods for injury repair, the agar underlay procedure allows the typical selective-medium colony morphology to develop and allows colonies to be more easily picked for further characterization. Higher recovery rates of heat-injured fecal enterococci from bovine fecal samples and total coliforms from animal waste lagoons were obtained by the agar underlay method with selective agars than by direct plating on the respective selective media.